IMPACT OF LEARNING ANALYTICS TOWARDS STUDENTS PERFORMANCE - Hisham, Syarifah Rabiyah Al Syed Badrul; Md Fadhil, Madihah; Rasul, Nazriah (PEOPLE: International Journal of Social Sciences, 2019)
The fast pace of big data analytics advancement makes it necessary for any organization to coincide it with their management and measurement process. It has become essential for education sectors to analyze this for the development of both learning and academic activities (Shikha. A, 2014). Learning analytics (LA) is the measurement and analysis of the collection of data with regards to learners and their context for making learning more effective. LA is much concern with improving learner’s success. Four dimensions have been identified; data and environment, stakeholders, objectives, and methods. This paper investigates the impact of learning analytics on student’s performance. The focus group was students in Technology Management program at UTM SPACE, Kuala Lumpur. Two research objective has been identified; (i) to find the level of LA understanding among academic staff and (ii) to investigate the relationship between learning analytics and student performance. The research focused on (i) data collection and population at Centre of Diploma Studies, UTM SPACE, KL; (ii) the selected sample will be students in Technology Management’s program; (iii) the research focused on learning analytics with main focus on course assessment reports of core course which are (a) technology management and (b) operation management.